2021
DOI: 10.3390/ijms22094485
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Oat Beta-Glucans in a Crohn’s Disease Model: Time- and Molar Mass-Dependent Effects

Abstract: Background: The incidence of Crohn’s disease (CD) is increasing worldwide, and it has currently become a serious public health issue in society. The treatment of CD continues throughout a patient’s lifetime, and therefore, it is necessary to develop new, effective treatment methods, including dietotherapy. The present study aimed to determine the effects of consumption of oat beta-glucans with different molar mass on colon inflammation (colitis) in the early stages of 2,4,6-trinitrobenzene sulfonic acid (TNBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
(87 reference statements)
3
15
1
1
Order By: Relevance
“…In addition, our study analyzed the influence of beta-glucans on the gene expression of important proteins involved in the pathogenesis of IBD. The results of this study, as well as that of the previously published works, confirm the immunomodulatory properties of both oat beta-glucan fractions [32,44,47]. However, high-molar-mass oat beta-glucan showed a stronger effect on the analyzed parameters and decreased the gene expression of Ccl3, Ccl4, Cxcl1, Cxcl2, Ccr1, Ccr2, Ccr5, Cxcr2, Osm, Csf3, and Spp1 in acute inflammation of the colon wall, and the gene expression of Ccl5, Cxcl1, Cxcl2, Cxcl11, Ccr2, Ccr5, Cxcr2, and Spp1 in the preremission phase (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, our study analyzed the influence of beta-glucans on the gene expression of important proteins involved in the pathogenesis of IBD. The results of this study, as well as that of the previously published works, confirm the immunomodulatory properties of both oat beta-glucan fractions [32,44,47]. However, high-molar-mass oat beta-glucan showed a stronger effect on the analyzed parameters and decreased the gene expression of Ccl3, Ccl4, Cxcl1, Cxcl2, Ccr1, Ccr2, Ccr5, Cxcr2, Osm, Csf3, and Spp1 in acute inflammation of the colon wall, and the gene expression of Ccl5, Cxcl1, Cxcl2, Cxcl11, Ccr2, Ccr5, Cxcr2, and Spp1 in the preremission phase (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…This effect is related to a faster and more intense immune response to the damage of the intestinal barrier caused by the rectal administration of TNSB. Our previously published results confirmed the accelerated remission and a milder course of inflammation in rats with colitis [32,39,44]. Interestingly, earlier studies have shown that neutrophils may also play a protective role during TNBS-and DSS-induced colitis [45,46].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…β-glucan regulates the gastrointestinal transit rate after meals and starch digestion to dilute blood sugar level through changes in the glycemic index, thereby reducing the insulinemic response in diabetes [ 41 , 45 ]. In addition, β-glucan has various physiological effects such as preventing cardiovascular diseases by controlling the blood pressure and anti-obesity and anti-cancer effects (e.g., prevention of colorectal cancer) [ 18 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. It lowers low-density lipoprotein (LDL) cholesterol level in the blood and elevates high-density lipoprotein (HDL) cholesterol level to help maintain normal blood lipid concentration and body weight [ 56 ].…”
Section: Functionality Of β-Glucan In Oatsmentioning
confidence: 99%